دور تقنيات محاسبة استهلاك الموارد في تحقيق السعر التنافسي وانعكاسه على تعظيم ربحية الشركة دراسة تطبـيقية في شركة الماس لصناعة الاسمنت – بازيان/ محافظة السليمانية - جاف, رزگار عبدالله صابر; حداد, ساز عبدالله محمد أحمد (Sulaimani Journal for Humanities, 2022)
The Purpose of this research aims to identify the extent of resource consumption accounting technique can be apply in allocating costs in comparison with other traditional costs and systems through analytical searching of the problems of applying traditional cost accounting systems and indicates the role of Resource Consumption Accounting technique as it is one of the modern cost technique that fits with the continuous development and changes in the business environment, including the scientific foundations that provides in allocating indirect industrial costs and determining the measurement of idol energy and costs. Moreover, the study concluded that the consumption accounting technique resources is a cost management tool that exploits costs through efficient use of available resources as aims to accurately measure the cost and provide appropriate information to the management that supports the decision-making process in order to reduce production costs, achieving customers desires, maximizing and the profitability of the company in a way that contributes to supporting its competitiveness. It aims mainly to accurately measure the cost and optimal use of the resources available to the profitable economic unit by reducing the cost per ton of ordinary cement (102101)dinars per ton according to the cost system applicable for Al-Mass company for cement industry to (96253.22) dinars per ton according to the technique of accounting consumption resources as for resistant cement and it's cost per ton has been reduced from (108028)dinars per ton according to the system costs applied in the unit to (9335.92) dinars per ton according to the resource consumption accounting technique. The reduction of production costs and the detection of idle energy to full fill the desires and needs of customers which lead to raising the efficiency of the company’s performance through increasing and maximizing the company’s profit.
Keywords: Resource Consumption Accounting; Proportional Cost; Fixed Cost; Competitive Price; Costs Reduction; Making Profit